Cash For Work? Extreme Poverty Solutions Based on Sustainable Development - Effendi, Ghina Nabilah; Purnomo, Eko Priyo; Malawani, Ajree Ducol (Universitas Negeri Semarang, 2020)
This article discusses how cash for work and the goals of sustainable development as solutions to extreme poverty. Lack of employment in villages is a factor in poverty in Indonesia. The cash for work program is an innovation of the central government and village government with village funds to provide productive activities to reduce poverty, and as a commitment of Indonesia to implement global goals, namely sustainable development goals. The research was conducted in the Village of Mekar Sari Ness, Village that implemented the program and faced challenges of poverty and unemployment. This study uses qualitative methods with descriptive statistical analysis using Nvivo12 plus data processing applications and using crosstab analysis. Sources of data obtained through government websites and application services, report documents, and journalism-related to the matter to be examined. This research concludes program cash for work can increase income per capita following SDGs standards, can open employment opportunities, especially for the rural poor and have a significant impact on optimizing village funds. Challenges going forward are managing village funds that must be in line with Ministry regulations, recruitment of workers and skills aimed at the poor and marginalized, as well as timeliness in implementing programs.